City of schemes - Thompson, Victoria (Victoria E.) (Thompson, Victoria (Victoria E.). Counterfeit lady novel, 2020)
"Elizabeth Miles is preparing for her wedding to Gideon Bates, when a menacing shadow from her past threatens to destroy the life she has built for herself in this all-new Counterfeit Lady Novel from USA Today bestselling author Victoria Thompson. The Great War is over, and Elizabeth and Gideon are busily planning their wedding and welcoming home old friends now discharged from the army. One of them, Captain Logan Carstens, the son and heir of a wealthy family, seems less than happy to be home and with good reason. While Logan was in France, he fell in love with a beautiful French woman named Noelle. He desperately wanted to propose, but he was already engaged and felt bound to honor his commitment. When Logan receives a letter supposedly from Noelle begging for money to help her flee the terrible conditions in France and come to America, Elizabeth is suspicious. There is no way to verify the letter is actually from Noelle, and she fears that a con man or woman might be trying to take advantage of Logan in his vulnerable state. But that is not all Elizabeth has to worry about. Vicious thug Oscar Thornton has gotten wind of her wedding announcement and realizes the woman who conned him is still alive and well. Gideon and Elizabeth have to figure out a way to help their friend while making sure their worst enemy does not destroy their future. . . "--Provided by publisher.